Tree-ring δ18Ocellulose variations in two Nothofagus species record large-scaleclimatic signals in the South American sector of the Southern Ocean - Soto Rogel, Pamela; Aravena, Juan Carlos; Villalba, Ricardo; Meier, Wolfgang Jens Henrik; Grießinger, Jussi (Palaeogeography, Palaeoclimatology, Palaeoecology)
In recent decades, southernmost South America (50–56° S) has experienced marked climate change (regional warming, decreased precipitation, reduced snow cover, and increased frequency of heat waves) related to variations in atmospheric circulation over varied timescales. In this paper, we develop oxygen isotopes from tree-ring cellulose (δ18OTRC) as a proxy for climate and atmospheric circulation in order to extend the regional meteorological record to deeper time intervals. Our work focuses on Nothofagus forests in two areas: (i) deciduous N. pumilio forest in the steppe transition zone near Punta Arenas and (ii) humid evergreen N. betuloides forest in the Navarino Island region. To investigate the potential for reconstructing palaeoclimate, δ18OTRC variations were correlated with local climate parameters as well as regional (Amundsen Sea Low, ASL) and hemispheric (Antarctic Oscillation, AAO) atmospheric circulation modes for the last 60 years. N. betuloides δ18OTRC variations show an overall positive trend, indicating isotopic enrichment over the study period, whereas no trend is recorded for the N. pumilio record. The strongest relationships with climate, together with the widest spatial representativeness, occur in the N. betuloides chronology during the growing season (spring to austral summer) and extend spatially from mid to high latitudes. In contrast, the sensitivity of the records is limited to summer months, and spatial correlations are much more limited. In addition, the N. betuloides record shows greater potential for reconstructing local climate features such as soil water (r = − 0.76), wind speed (r = 0.69), and precipitation (r = − 0.66), as well as regional (ASL, r = − 0.80) and hemispheric (AAO, r = 0.77) patterns of extratropical atmospheric circulation. Overall, we conclude that the N. betuloides record represents the most valuable tree-ring climate proxy for southernmost South America over past centuries. Fil: Soto Rogel, Pamela. Universidad de Magallanes; Chile. Universitat ...